On Refusing Canada, Canlit and More: National and Literary Identity in All Its Varieties - Ravvin, Norman (Studia Anglica Posnaniensia, 2020)
Two recent anthologies of Canadian writing – Refuse: CanLit in Ruins and Resisting Canada: An Anthology of Poetry – reflect stances of resistance to mainstream institutional understandings of Canadian writing culture. They highlight recent scandals in academia and in literary communities, as well as highlighting the voices of Indigenous and women writers. These stances echo earlier forms of cultural revolution in Canada, in particular the Refus global manifesto, which provoked conventional Quebec society in the late 1940s. This paper contrasts these forms of refusal with a period in the 1950s and 1960s when influential Jewish writers, including Leonard Cohen and Irving Layton, took a counter-cultural stance while appearing in mainstream venues offered to them by CBC television and radio.